2018
DOI: 10.7717/peerj.5890
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of sex and handedness on the Wisconsin Card Sorting Test: the contradiction between neuroimaging and behavioural results

Abstract: This study investigated the potential role of sex and handedness on the performance of a computerised Wisconsin Card Sorting Test (WCST) in healthy participants by applying functional near-infrared spectroscopy (fNIRS). We demonstrated significant (p < 0.05) sex-related differences of hemodynamic response in the prefrontal cortex of 70 healthy participants (female, n = 35 and male, n = 35; right-handed, n = 40 and left-handed, n = 30). In contrast, behavioural results of the WCST do not show sex bias, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 91 publications
2
4
0
Order By: Relevance
“…The cognitive performance of five different tasks were not significantly different between the sitting and leaning workstations, which was not consistent with the results of the fNIR data. This indicates that changes of hemodynamic activity in the prefrontal cortex may not necessarily relate to the behavior outcomes of cognitive tasks, which was similar to the previous study's finding during Wisconsin Cart Sort task [34]. Moreover, we only recruited healthy young university students.…”
Section: Discussionsupporting
confidence: 74%
“…The cognitive performance of five different tasks were not significantly different between the sitting and leaning workstations, which was not consistent with the results of the fNIR data. This indicates that changes of hemodynamic activity in the prefrontal cortex may not necessarily relate to the behavior outcomes of cognitive tasks, which was similar to the previous study's finding during Wisconsin Cart Sort task [34]. Moreover, we only recruited healthy young university students.…”
Section: Discussionsupporting
confidence: 74%
“…It is noteworthy that males and females differ significantly during resting state – men demonstrated a higher HbO (Jaušovec and Jaušovec, 2010; Chuang and Sun, 2014). In the present study, the two-way stress and gender interaction in the right lateral PFC with a medium effect size (η p 2 = 0.385) revealed higher HbO in males than females under stress, results consistent with Li et al (2010) and Cinciute et al (2018). Greater HbO in males than females may have been due to increased neuronal activation or differences in brain and morphology (Ruigrok et al, 2014; Choleris et al, 2018).…”
Section: Discussionsupporting
confidence: 71%
“…Perhaps the relative low number of subjects following stratification by education in each education group prevents us from detecting sex differences in these two scores [ 16 ]. Interestingly, Cinciute et al [ 17 ] identified significant sex-related neuronal activity in the PFC in healthy participants, but behavioral results of the WCST did not show sex bias. This contradiction arises because some functional brain maps of the WCST may be sensitive to neurophysiology heterogeneity which is not apparent or necessarily related to the behavior [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Cinciute et al [ 17 ] identified significant sex-related neuronal activity in the PFC in healthy participants, but behavioral results of the WCST did not show sex bias. This contradiction arises because some functional brain maps of the WCST may be sensitive to neurophysiology heterogeneity which is not apparent or necessarily related to the behavior [ 17 ]. Although the standardization, validity and reliability of WCST as a stand-alone cognitive assessment in healthy adults of various ages and education levels have been established [ 72 ], a battery of cognitive tests is required to unveil the effects of education on different domains of cognition.…”
Section: Discussionmentioning
confidence: 99%